Self-esteem and professional identity of early education teachers - Valero-Ancco, Vidnay N. (2021)
In recent times private entities began to take care of the personal aspects of their collaborators, so in the processes of selection of personnel the soft skills possessed by the applicants is taken into account, and in relation to the permanent staff is tracked their emotional state, levels, stress, satisfaction with work, etc. In the state sector it is an obligation of the state to assume similar concerns for public employees, especially teachers, as they are responsible for conducting education in the country, therefore they must be cared for in personal aspects, such as assessing and strengthening the levels of self-esteem of teaching staff, as well as promoting a high professional identity , which results in better performances and therefore better learnings in students. Given the importance of these variables, this research aims to determine the relationship between the self-esteem and professional identity of teachers at the initial level of Urubamba, 2019. It worked under the quantitative approach with a type of non-experimental research and cross-cutting correlal design. The population consists of 45 teachers. The results indicate that there is a moderate positive correlation between self-esteem and proven professional identity with a Pearson R value of 0.503 and corroborated with the hypothesis test in which the value of p<0.05 (0.00<0.05).